(untitled) - Ana Marija Hošnjak; Jana Goriup (University of Ostrava, 2024)
Aim: This study aimed to test an existing theory of the Anxiety about Aging Scale and determine the relationship between ageism and anxiety about aging in nurses in the Republic of Croatia. Design: A cross-sectional study. Methods: The sample consisted of 798 nurses from Republic of Croatia. Participants filled Anxiety about Aging Scale and Kogan's Attitude toward Old People Scale. Results: Regarding the factor structure of the 20 items, chi-square test revealed a statistically significant finding (χ2 = 2131.090, df = 164, p > 0.05). Analyses confirmed the four-factor structure (fear of older adults, psychological concern, fear of loss, and physical appearance) and the indicators of adequate reliability and validity. Furthermore, Kogan's Attitude toward Old People Scale significantly correlated with fear of older adults (r = 0.409; p < 0.01); attitudes changed with fear of older adults. Factors such as age, work experience duration (in years), and education individually affected aging anxiety, but not sex, living with older adults, and work department. Conclusion: The Anxiety about Aging Scale Croatian version is a valid and reliable measuring instrument for nurses. Nurses who have expressed greater anxiety about aging have a more negative attitude toward older adults.